The effect of growth temperatures and substrate orientations of indium gallium phosphide quantum wires - Nor Helmi, Nor Hamizah (2014)
Indium gallium phosphide (InGaP) nanowires were grown on gallium arsenide (GaAs) substrate by using metal-organic chemical vapour deposition (MOCVD) via vapour-liquid-solid (VLS) technique. The grown InGaP wires were characterized by using scanning electron microscopy (SEM), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDX). The results showed that the growth of the InGaP wires depend strongly on the growth temperatures and substrate orientations. At low temperature of 380°C, wires grown on GaAs substrates were almost cylinderlike, while with increasing temperatures ranging from 410-500°C, the reversetapering phenomenon occurred producing microphone-like InGaP nanowires. With increasing temperature from 380-500°C, Au alloy-seed particle or the head part of the InGaP nanowires were also observed to be thicker in diameter (85-452 nm) than the body part (49.2-224.3 nm), which had been proven by the chemical compositions percentage in EDX analysis. Wires grown on GaAs (100) substrate were less than number of wires on GaAs (111) B substrate although wires on both substrates are basically grown on random directions. Twin boundaries crystal defects have been detected on some of the InGaP nanowires structures from TEM analysis. Such defects are not good and should be avoided to prevent further problem when being incorporated into potential devices. The crystal structure for all samples of InGaP wires is zinc blende (ZB), the lattice spacing (d) of InGaP wires is 3.342A, and the lattice parameter (a) is 5.788A.